Development Of the Sinau Karakter Lumantar Dongeng Book in Reading Literacy Learning for Junior High School Students - Emi Sudarwati; Afendy Widayat (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2025)
Based on the documentation study of AKM (Minimum Competency Assessment) scores and preliminary interviews with AKM supervisors, it was found that the reading literacy ability of students at SMPN 1 Baureno is still relatively low. This study aims to: (1) analyze the needs for the Sinau Karakter Lumantar Sinau Karakter Lumantar Dongeng book; (2) develop a prototype of the Sinau Karakter Lumantar Sinau Karakter Lumantar Dongeng book; and (3) describe the validation of the Sinau Karakter Lumantar Sinau Karakter Lumantar Dongeng book. The research was conducted at SMPN 1 Baureno using the 4D (Define, Design, Develop, Disseminate) research and development model developed by Thiagarajan. Data collection techniques included observation, interviews, and questionnaires, while data analysis was carried out using qualitative and quantitative approaches. The results of the study indicate that the low reading literacy among students is caused by the lack of engaging, contextual, and culturally based fiction reading materials. Therefore, it is necessary to develop a book based on local Bojonegoro folktales for seventh-grade students. The prototype of the Sinau Karakter Lumantar Sinau Karakter Lumantar Dongeng book was designed in alignment with the national curriculum in the form of a printed book containing 16 local folktales, discussion activities, AKM-based exercises, and 14 character education values. The validation test results showed a very high level of feasibility, with scores of 97% for material validation, 94% for teaching material, and 93% for media. This study demonstrates that the Sinau Karakter Lumantar Sinau Karakter Lumantar Dongeng book is suitable for use as a learning medium to improve students’ reading literacy and instill character values. The use of this book can also serve as an alternative teaching material that is contextual and relevant to the local culture within the school environment.